Effects of inherited cores and magmatic overgrowths on zircon (U‐Th)/He ages and age‐eU trends from Greater Himalayan sequence rocks, Mount Everest region, Tibet. (7th August 2015) - Orme, Devon A.; Reiners, Peter W.; Hourigan, Jeremy K.; Carrapa, Barbara
Abstract: Previous constraints on the timing and rate of exhumation of the footwall of the South Tibetan detachment system (STDS) north of Mount Everest suggest rapid Miocene cooling from ∼ 700°C to 120°C between ∼14–17 Ma. However, 25 new single grain zircon He ages from leucogranites intruding Greater Himalayan Sequence rocks in the footwall of the STDS are between 9.9 and 15 Ma, with weighted mean ages between 10 and 12 Ma. Zircon grains exhibit a positive correlation between age and effective uranium (eU). Laser ablation zircon U‐Pb geochronology, detailed SEM observations, and laser ablation depth‐profiling of these zircons reveal low‐eU 0.5–2.5 Ga inherited cores overgrown by high‐eU 17–22 Ma rims. This intragranular zonation produces ages as much as 32% too young when a standard alpha‐ejection correction assuming uniform eU distribution is applied. Modeling of the effects of varying rim thickness and rim eU concentration on the bulk grain eU and alpha‐ejection correction suggests that zonation also exerts the primary control on the form of the age‐eU correlation observed. Application of grain‐specific zonation‐dependent age corrections to our data yields zircon He ages between 14 and 17 Ma, in agreement with AFT and 40 Ar/ 39 Ar ages. Growth of magmatic rims followed by cooling to < 120°C within 1–6 million years supports rapid tectonic exhumation associated with slip along the STDS in the Miocene. This study highlights the importance of characterizing parent nuclide zonation in zircon He studies which seek to understand the timing of exhumation along exhumed crustal blocks. Key Points: Zircon He ages from the footwall of the STDS have extreme intragranular zonation Zonation produces ages which are too young and controls the age‐eU trend Zonation‐dependent age corrections yield ages supporting rapid cooling, 14–17 Ma